2021
DOI: 10.1021/acsami.1c12592
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rolling of Monolayer Graphene for Ultrasensitive Molecular Sensing

Abstract: The controllable manipulation of graphene to create three-dimensional (3D) structures is an intriguing approach for favorably tuning its properties and creating new types of 3D devices. However, due to extremely low bending stiffnesses, it is rather challenging to construct monolayer graphene into stable 3D structures. Here, we demonstrate the stable formation of monolayer graphene microtubes with accompanying pre-patterned strain layers. The diameter of graphene microtubes can be effectively tuned by changing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The size of graphene wrinkles ranges from the micrometer to the nanometer scale. Although micrometer-sized wrinkles have been studied using conventional Raman spectroscopy, nanometer-sized wrinkles are well-below the diffraction limit and cannot be resolved by diffraction-limited Raman microscopes whose spatial resolution is a few hundreds of nanometers at best. In order to observe and analyze these minute features of graphene, a super-resolution technique called tip-enhanced Raman spectroscopy (TERS) is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The size of graphene wrinkles ranges from the micrometer to the nanometer scale. Although micrometer-sized wrinkles have been studied using conventional Raman spectroscopy, nanometer-sized wrinkles are well-below the diffraction limit and cannot be resolved by diffraction-limited Raman microscopes whose spatial resolution is a few hundreds of nanometers at best. In order to observe and analyze these minute features of graphene, a super-resolution technique called tip-enhanced Raman spectroscopy (TERS) is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The self-rolling of monolayer graphene not only results in a larger surface area compared to monolayer graphene but also allows for further enhancement by increasing the number of turns in the rolled structure. Ma et al 43 demonstrated the fabrication of 3D tubular structures by depositing strain layers, providing the necessary driving force and support for rolling up monolayer graphene into graphene microtubes (Fig. 2(c)).…”
Section: Strategies For Improving the Electrical And Mechanical Prope...mentioning
confidence: 99%
“…Therefore, the bending stiffness of single-layered graphene is very close to the lipid bilayers in cells with extremely low bending rigidity (≈1-2 N m −2 ) of the out-of-plane deforma-tion, which is too "soft" to control its morphology and construct stable 3D structures without a supporting substrate in real applications. [22][23][24][25] On the other hand, it is easily susceptible to the destruction of in-plane deformation because the peak tensile strain of the free-standing single-crystalline monolayer graphene is just 5.8% before fracture, with a minimal fracture strength of less than 150 μN and an extremely low tensile stiffness of only ≈350 N m −1 in practical tensile tests. [21] These parameters lead to a poor resistance of the graphene film during tension and bending.…”
Section: Introductionmentioning
confidence: 99%